Silviculture for sustainable forest management in Nepal - Adhikari, Shankar (Banko Janakari, 2018)
Not available. BANKO JANAKARI A Journal of Forestry Information for Nepal Special Issue on Silviculture Special Issue No. 4, 2018, page: 1-5